The forensic casebook : the science of crime scene investigation - Genge, Ngaire (New York : Ballantine ; London : Turnaround [distributor], 2002)
'The Forensic Casebook' draws on interviews with police personnel and forensic scientists - including animal examiners, botanists, zoologists, firearms specialists and autoposists - to uncover the vast and detailed under-workings of criminal investigation.
Includes bibliographical references (p. 304-311) and index.
Keywords: Forensic sciences; Crime scene searches; Crime scenes; Evidence, Expert; Crime